Efektifitas Pemberantasan Tindak Pidana Perjudian Online Melalui Situs Pusatkoin di Wilayah Hukum Direktorat Reserse Kriminal Khusus Polda DIY: Penelitian - Hernanda Pramana Adji; HM. Zaki Sierrad; Elza Qorina Pangestika (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The phenomenon that occurs in society of gambling crimes, including online gambling, is a serious problem in Indonesia that is difficult to eradicate, even though it has become a criminal act. Gambling, especially online gambling, continues to grow along with the advancement of information technology, and its impacts cover various aspects, including economic, psychological, and social. Empirical legal research consists of research on legal identification and research on legal effectiveness.